Boosting Chemodynamic Therapy by the Synergistic Effect of Co-Catalyze and Photothermal Effect Triggered by the Second Near-Infrared Light - Zhang, Songtao; Jin, Longhai; Liu, Jianhua; Liu, Yang; Zhang, Tianqi; Zhao, Ying; Yin, Na; Niu, Rui; Li, Xiaoqing; Xue, Dongzhi; Song, Shuyan; Wang, Yinghui; et al. (Nano-Micro Letters, 2020)
In spite of the tumor microenvironments responsive cancer therapy based on Fenton reaction (i.e., chemodynamic therapy, CDT) has been attracted more attentions in recent years, the limited Fenton reaction efficiency is the important obstacle to further application in clinic. Herein, we synthesized novel FeO/MoS2 nanocomposites modified by bovine serum albumin (FeO/MoS2-BSA) with boosted Fenton reaction efficiency by the synergistic effect of co-catalyze and photothermal effect of MoS2 nanosheets triggered by the second near-infrared (NIR II) light. In the tumor microenvironments, the MoS2 nanosheets not only can accelerate the conversion of Fe3+ ions to Fe2+ ions by Mo4+ ions on their surface to improve Fenton reaction efficiency, but also endow FeO/MoS2-BSA with good photothermal performances for photothermal-enhanced CDT and photothermal therapy (PTT). Consequently, benefiting from the synergetic-enhanced CDT/PTT, the tumors are eradicated completely in vivo. This work provides innovative synergistic strategy for constructing nanocomposites for highly efficient CDT. Highlights 1 The MoS2 nanosheets served as co-catalyst could reduce Fe3+ ions with lower Fenton reaction activity into the highly reactive Fe2+ ions, thereby boosting the production of hydroxyl radical (•OH) for high efficiency chemodynamic therapy (CDT). 2 The photothermal effect of MoS2 nanosheets motivated by second near-infrared light could further improve the treatment effectiveness by synergetic photothermal-enhanced CDT and photothermal therapy.